Al-Tawassut waal-I‘tidal: Menjawab Tantangan Liberalisme dan Konservatisme Islam - DR. IRAWAN, M.S.I (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2018)
The purpose of this paper is to explain al-tawassut wa al-i‘tidal in answering the challenge of Islamic liberalism. The presence of Islamic liberalism is seen by Islamic fundamentalism as a notion that prioritizes rationality and beyond the teachings of Islam in understanding the texts of the Qur’an. On the contrary, Islamic liberalism views Islamic fundamentalism as too restrained in the freedom of thought to eliminate the reasoning capabilities that God gives to humans. Through historical analysis and phenomena occurring in the religious life of Muslims, this paper explains the important role of understanding al-tawassut wa al-i‘tidal as the middle path of religion. Moderate (wasatiyah) covers various as- pects: religiosity, spirituality, intellectuality, appearance, attitude, behavior, rela- tions and activities of Muslims in the contemporary era. Various aspects of life must be understood by multi-knowledge in order to avoid ultra-liberal thinking and extremist interpretation. Al-tawassut wa al-i‘tidal is an interpretation of the Qur’an (Surat al-Baqarah: 143) and the hadith of the Prophet for Muslims to be “balance and justice”. In addition, altawassut wa al-i‘tidal combines the “tradi- tions” (al-muhafazah) and “tajdid” (al-akhzu).This paper concludes that al-tawassut wa al-i‘tidal educates Muslims to be tolerant, just, democratic, and not self-righ- teous. If every Muslim understands Islam “moderately” and “justly”, so the truth claim will not happen and ummatan wasat}an will be realized.This paper, theo- retically, is expected to contribute a comprehensive- constructive knowledge in understanding Islamic religious texts. Likewise, practically, the arguments and analysts of this paper become the reference for every ism in Islam to be balanced and justice in religion.